LEGAL PROTECTION POLICY FOR CHILDREN AS RAPE VICTIM IN GETTING REHABILITATION SERVICES - Antory Royan Adyan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis study focused on identifying the rules or norms of positive law, relating toArticle 64 paragraph (3) letter a of Law No.23 of 2002 carried throughÂ  rehabilitation efforts, both within the institution and outside the institution. Background inequity of treatment between the rights of offenders and the rights of victims in the criminal justice system. positive in criminal law today is more emphasis on the protection of nonphysical rehabilitation of mental disorder be done "in abstracto" or indirectly berdasakan legal system in Indonesia embraces the Civil Law system, which is based on the written law (written law) and poured as much as possible the norm to the rule of law. Special protection policy that ensures the future of the child victims of crime, in Article 64 paragraph (3) letter a of Law No.23 of 2002, it is necessary written law. Indonesia's civil law system adopted should be clearly mentioned and detailed in order to ensure legal certainty in providing maintenance support services and child care, medical, health care and physical rehabilitation of child psychology. Through the decisionÂ  of the judge in imposing its decision based on the principles of organization of the judiciary, in article 2, paragraph (2) No. 48 Year 2009, the Court declared the state to implement and enforce the law and justice based on Pancasila, to implement the provisions of Article 64 paragraph (3) letter a of Law no. 23 of 2002.Key Word : Protection, Law , Childs Victims, Rehabilitation